Stepping into Who I Fully Am: A Creative Exploration of Autistic Menopause - Mx Rose Matthews; Christine A. Jenkins; Margaret Janse van Rensburg; Miranda J. Brady; Rachel L. Moseley; Julie M. Gamble-Turner (International Journal of Disability and Social Justice, 2025)
Research suggests that perimenopause can compound existing struggles for some Autistic people, with potentially catastrophic consequences. Barriers to self-expression due to communication differences are also well-documented. Acknowledging this, our neurodiverse research team invited creative submissions themed around Autistic experiences of menopause, receiving works from six Autistic participants including paintings, poetry, and graphic works. Engaging with the six creative submissions, Autistic Community Researchers on our team produced reflexive, polytextual response works. Creative exploration of Autistic menopause encouraged emotional catharsis, self-understanding, and activism/artivism. Autistic Community Researchers noted transcendent, almost “magical” dimensions of connecting with other Autistic people’s lived experiences. Our creative emancipatory approach enabled Autistic, multimedia responses which traditional research methods would not have elicited. To our knowledge, no other studies to date have used arts-based research to explore Autistic people’s experiences of menopause and inclusive research practices.